The Influence of Economic Growth, Investment, and Min-imum Wage on Unemployment in East Kalimantan Districts - Ahmad Shofyuddin; Wiwin Priana Primandhana (Global Economics: International Journal of Economic, Social and Development Sciences, 2025)
This study investigates the influence of economic growth, investment, and minimum wage on the open unemployment rate across districts and cities in East Kalimantan Province. The research employs a quantitative descriptive approach with panel data regression analysis, processed using EViews 13 software. Model selection was carried out through the Chow and Hausman tests, which identified the Fixed Effect Model (FEM) as the most appropriate estimation technique. The study utilizes secondary data from 2018 to 2024, obtained from the Central Bureau of Statistics (BPS) and the Investment and One-Stop Integrated Service Office of East Kalimantan Province. The empirical findings demonstrate that economic growth exerts a negative and statistically significant impact on the open unemployment rate, indicating that higher economic growth effectively contributes to reducing unemployment in the region. Foreign Investment (PMA) is found to have a negative but insignificant effect, suggesting that inflows of foreign capital alone do not directly translate into job creation unless accompanied by supporting policies and local labor absorption capacity. In contrast, Domestic Investment (PMDN) shows a positive yet statistically insignificant relationship with unemployment, reflecting the possibility that domestic investments may not always generate sufficient employment opportunities in the short term due to structural constraints or sectoral imbalances. Furthermore, the minimum wage variable has a negative and significant effect on the open unemployment rate, implying that increases in the regional minimum wage can stimulate greater employment absorption and improve labor market conditions. Overall, the results highlight the importance of fostering sustained economic growth and designing investment policies that are more labor-intensive to optimize employment creation. Additionally, the findings emphasize the strategic role of minimum wage policy in supporting job opportunities while safeguarding workers’ welfare.